Development and recovery of iron deficiency by iron resupply to roots or leaves of strawberry plants - Pestana, M. (2012)
Bare-root transplants of strawberry (Fragaria ananassa Duch. cv. ‘Selva’) were transferred to nutrient solutions with or without iron (Fe). After six weeks of growth, plants grown in solution lacking Fe were chlorotic and showed morphological changes in roots typical of Fe deficiency. Subsequently, four treatments were applied for nine days: plants grown in continued absence of Fe (Fe0); plants grown in continued presence of 10 mM Fe (Fe10); foliar application of ferrous sulphate every two days to chlorotic plants (Fe-leaves); and growth of chlorotic plants in solution with ferrous sulphate (Fe-solution). After six days, the chlorophyll (Chl) content in leaves of Fe-solution plants was similar to that in Fe10 plants. Under the Fe-leaves treatment, a slight regreening of new leaves was observed only by the end of the experiment. After nine days, ferric chelate reductase (FC-R) activity was unchanged in Fe10 but increased in Fe0 plants. The FC-R activity of Fe-solution plants was similar to the initial value for chlorotic plants, whereas it was reduced drastically under the Fe-leaves treatment. The Fe concentration in leaves of Fe0 and Fe10 was similar, whereas the Fe-solution and Fe-leaves treatments enhanced leaf Fe concentration. In contrast to the Fe-solution treatment, foliar application of Fe did not increase the Fe concentration in roots. Under our experimental conditions, FC-R activity in strawberry appeared to be deactivated rapidly by pulses of Fe applied by foliar sprays. Deactivation was slower if Fe was applied directly to roots, which suggested that the plants had greater opportunity to take Fe.